Economic pluralism in the study of wage discrimination: a note - Drydakis, Nick (Bonn, 2018)
"Economic pluralism proposes that economists and social planners should consider alternative theories to establish a range of policy actions. Neoclassical, Feminist and Marxian theories evaluate well-grounded causes of wage discrimination. Racist attitudes, uncertainties regarding minority workers' productivity and power relations in lower-status sectors might generate discriminatory wages. Each cause deserves corresponding policy action. Given pluralism, wage discrimination might be reduced by implementing equality campaigns, creating low-cost tests to predict workers' productivity and abolishing power relations towards minority workers. Pluralism might be jeopardised if there is a limited desire to engage with less-dominant theoretical frameworks. Also, pluralism might be misled with rejection of dominant theories."